2007
DOI: 10.3748/wjg.v13.i15.2166
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic and prophylactic thalidomide in TNBS-induced colitis: Synergistic effects on TNF-α, IL-12 and VEGF production

Abstract: AIM:To evaluated the therapeutic and prophylactic effect of thalidomide on 2, 4, 6-trinitrobenzene sulfonic acid (TNBS)-induced colitis. Thalidomide has been reported to downregulate the expression of tumor necrosis factor α (TNF-α), IL-12, and vascular endothelial growth factor (VEGF), hallmarks of intestinal inflammation in Crohn's disease (CD). METHODS:Male Wistar rats were divided in five groups of ten animals each. Four groups received a rectal infusion of TNBS in ethanol. The first group was sacrificed 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 48 publications
1
15
0
1
Order By: Relevance
“…A comparable anti-inflammatory effect of D-JNKI-1 was previously described by our group19 in an acute form of severe TNBS colitis, which is an acute model of IBD with pathophysiological properties similar to those of Crohn’s disease 5153. Simultaneous subcutaneous application of D-JNKI-1 significantly reduced the DAI scores.…”
Section: Discussionsupporting
confidence: 75%
“…A comparable anti-inflammatory effect of D-JNKI-1 was previously described by our group19 in an acute form of severe TNBS colitis, which is an acute model of IBD with pathophysiological properties similar to those of Crohn’s disease 5153. Simultaneous subcutaneous application of D-JNKI-1 significantly reduced the DAI scores.…”
Section: Discussionsupporting
confidence: 75%
“…Intravesical corticotropinreleasing hormone and acute restraint stress induce mast celldependent VEGF release from bladder explants (7). VEGF can bind and stimulate inflammatory cells (43), and proinflammatory cytokines (e.g., IL-1␤ and TNF␣) can induce VEGF protein expression (2,8,43). In addition, bladder biopsies from IC patients with glomerulations following hydrodistension show increased expression of VEGF protein (52).…”
mentioning
confidence: 99%
“…For instance, the expression levels of VEGF-A are increased in the colonic mucosa, serum, and plasma of IBD patients compared with the healthy controls (2,3). In line with this observation, experimental mouse colitis is ameliorated by inhibition of VEGF expression and/or activity with neutralizing antibodies or thalidomide treatment (4,5). Even though emerging evidence indicates an important role of VEGF in regulating IBD, the molecular mechanism by which VEGF regulates colonic inflammation is still under investigation.…”
Section: Vascular Endothelial Growth Factor (Vegf)mentioning
confidence: 83%
“…Intriguingly, it has been previously suggested that increased expression level of VEGF could promote intestinal inflammation in animal and clinical studies (2)(3)(4)(5). In light of this contention, we hypothesized that CREB Ϫ/Ϫ mice would express less VEGF than CREB ϩ/ϩ mice and thereby exhibit less severe inflammatory response than the wild type control.…”
Section: Regulation Of Vegf Promoter Activity By the Crh Family Ismentioning
confidence: 89%